A new water mite species of the Hygrobates fluviatilis-complex from Russia (Acari, Hydrachnidia, Hygrobatidae) - Tuzovskij, Petr V. (Zootaxa, 2021)
The Hygrobates fluviatilis-complex includes the following ten species:H. fluviatilis (Ström, 1768), H.arenarius Smit & Pešić, 2017, H.corsicus Pešić& Smit, 2017, H. marezaensis Pešić & Dabert, 2017,H. turcicus Pešić, Esen & Dabert, 2017, H. persicus Pešić &Asadi, 2017, H. grabowskii Pešić, Saboori, Zawal & Dabert, 2019,H. ulii Pešić, Saboori, Zawal & Dabert, 2019, H. balcanicus Pešić, 2020 and H. mediterraneus Pešić, 2020 (Pešić et al. 2017, 2019, 2020, respectively).This paper gives the description of one further new species of the genus, based on material collected by the author in running waters of the European part of Russia. The material was sampled with a hand net with 250 μm mesh side. Specimens were not fixed in Koenike liquid, but slides were made from fresh material. Idiosomal setae are named according to Tuzovskij (1987). The following abbreviations are used: H—height, L—length; ml—medial length, n—number of specimens measured; P-1-5, pedipalp segments (trochanter, femur, genu, tibia and tarsus); W—width; I-IV-Leg-1–6, first leg, segments 1–6 (trochanter, basifemur, telofemur, genu, tibia and tarsus) i.e. III-Leg-3 = genu of third leg.All measurements are given in micrometers(μm), length of appendage segments is given as dorsal length. The type material is deposited in the collection of the Papanin Institute for Biology of Inland Waters (Borok, Russia).